Influence of Ni/CeO2 on Pyrolytic Conversion of FOBS to Hydrogen Formation - Wan Nur Anis Amira Wan Ranizang; Mazura Jusoh; Mohd Asmadi; Zaki Yamani Zakaria (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Fuel Oil Blended Stock (FOBS) is a residual byproduct from petroleum refineries that is often underutilized and may cause storage and environmental issues. Converting FOBS into hydrogen through catalytic pyrolysis offers a sustainable waste valorisation pathway; however, no studies have focused on Ni/CeO2 catalysts for hydrogen production from FOBS, which establishes the novelty of this work. This study aims to evaluate the performance of a Ni/CeO2 catalyst for hydrogen production from FOBS via catalytic pyrolysis. A 3% Ni/CeO2 catalyst was synthesized using the wet impregnation method and characterized using XRD, FESEM, BET, and FTIR. Catalytic pyrolysis experiments were conducted in a tubular furnace reactor at temperatures between 400-600 °C, nitrogen flow rates of 40-140 mL/min, and catalyst-to-feedstock ratios of 1:5, 1:10, and 1:15. The gaseous products were analyzed using GC-TCD/FID. The results showed that higher temperatures and catalyst-to-feedstock ratios improved FOBS conversion and hydrogen selectivity, with optimal performance achieved at 600 °C, 90 mL/min, and a catalyst-to-feedstock ratio of 1:15, yielding high conversion, gas yield, and hydrogen selectivity. In conclusion, the Ni/CeO2 catalyst shows strong potential for converting FOBS into hydrogen-rich gas, supporting waste valorisation and sustainable hydrogen production. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).